Response of macrophage Toll-like receptor 4 to a Sporothrix schenckii lipid extract during experimental sporotrichosis - Sassa, Micheli F. [UNESP]; Saturi, Ana E. T. [UNESP]; Souza, Lucas F. [UNESP]; de Abreu Ribeiro, Livia C. [UNESP]; da Graca Sgarbi, Diana B.; Carlos, Iracilda Zeppone [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>Toll-like receptors have been implicated in the recognition of various pathogens, including bacteria, viruses, protozoa and fungi. However, no information is available about Toll-like receptor 4 (TLR4) participation in Sporothrix schenckii recognition and the consequent triggering of the immune response to this fungal pathogen. Following activation of TLRs by ligands of microbial origin, several responses are provoked, including reactions in immune cells that may lead them to produce signalling factors that trigger inflammation. The present study was designed to elucidate the role of TLR4 during the host response to S. schenckii. TLR4-deficient (C3H/HeJ) and control mice (C3H/HePas) were infected with S. schenckii yeast cells and immune response was assessed over 10 weeks by assaying production of pro-inflammatory mediator (nitric oxide and tumour necrosis factor-alpha) and anti-inflammatory cytokine (interleukin-10) by peritoneal macrophages and their correlation with apoptosis in peritoneal exudate cells. We found that both pro-inflammatory and anti-inflammatory mediators are reduced in TLR4-deficient mice, suggesting the involvement of this receptor in the recognition of this infectious agent. Translocation into the nucleus of nuclear transcription factor, nuclear factor-kappa B, was also evaluated and showed higher levels in TLR-4 normal mice, consistent with the results found for cytokine production. We are showing here, for the first time, the involvement of TLR4 in S. schenckii recognition. Taken together, our results demonstrate that the activation of peritoneal macrophages in response to S. schenckii lipid extracts has different responses in these two mouse strains which differ in TLR4 expression, suggesting an important role for TLR4 in governing the functions of macrophages in this fungal infection.
Keywords: apoptosis; cytokines; fungal infection; nitric oxide; toll-like receptor 4